Future water quality monitoring--adapting tools to deal with mixtures of pollutants in water resource management - Altenburger, Rolf; Ait-Aissa, Selim; Antczak, Philipp; Backhaus, Thomas; Barceló, Damià; Seiler, Thomas-Benjamin; Brion, Francois; Busch, Wibke; Chipman, Kevin; de Alda, Miren López; de Aragão Umbuzeiro, Gisela; Escher, Beate I; et al. (The Science of the total environment, 2015)
Environmental quality monitoring of water resources is challenged with providing the basis for safeguarding the environment against adverse biological effects of anthropogenic chemical contamination from diffuse and point sources. While current regulatory efforts focus on monitoring and assessing a few legacy chemicals, many more anthropogenic chemicals can be detected simultaneously in our aquatic resources. However, exposure to chemical mixtures does not necessarily translate into adverse biological effects nor clearly shows whether mitigation measures are needed. Thus, the question which mixtures are present and which have associated combined effects becomes central for defining adequate monitoring and assessment strategies. Here we describe the vision of the international, EU-funded project SOLUTIONS, where three routes are explored to link the occurrence of chemical mixtures at specific sites to the assessment of adverse biological combination effects. First of all, multi-residue target and non-target screening techniques covering a broader range of anticipated chemicals co-occurring in the environment are being developed. By improving sensitivity and detection limits for known bioactive compounds of concern, new analytical chemistry data for multiple components can be obtained and used to characterise priority mixtures. This information on chemical occurrence will be used to predict mixture toxicity and to derive combined effect estimates suitable for advancing environmental quality standards. Secondly, bioanalytical tools will be explored to provide aggregate bioactivity measures integrating all components that produce common (adverse) outcomes even for mixtures of varying compositions. The ambition is to provide comprehensive arrays of effect-based tools and trait-based field observations that link multiple chemical exposures to various environmental protection goals more directly and to provide improved in situ observations for impact assessment of mixtures. Thirdly, effect-directed analysis (EDA) will be applied to identify major drivers of mixture toxicity. Refinements of EDA include the use of statistical approaches with monitoring information for guidance of experimental EDA studies. These three approaches will be explored using case studies at the Danube and Rhine river basins as well as rivers of the Iberian Peninsula. The synthesis of findings will be organised to provide guidance for future solution-oriented environmental monitoring and explore more systematic ways to assess mixture exposures and combination effects in future water quality monitoring.
Keywords: Mixture toxicity; kvalita vody; monitorování životního prostředí; Water Quality; Environmental Monitoring; Chemical status; Water Resources; zachování přírodních zdrojů; Water Pollutants, Chemical; Priority chemicals; WFD; Water quality; Effect-based tools; vodní zdroje; chemické látky znečišťující vodu; Conservation of Natural Resources; Ecological status